Gambaran Praktik Pencegahan Komplikasi Pada Penderita Diabetes Melitus Tipe 2 Di Puskesmas Kecamatan Jepara - Prameswari, Nissa shakira Ayudya (Jurnal Riset Kesehatan Masyarakat, 2025)
Diabetes mellitus is a degenerative disease that occurs due to the unbalanced amount of insulin in the body Type 2 diabetes mellitus is a metabolic process disorder characterized by increased blood sugar levels, diabetes is still a non-communicable disease with a high number of cases per year. The high number of type 2 diabetes mellitus is also followed by an increase in the number of cases of type 2 diabetes mellitus complications. The number of diabetes mellitus type 2 complication in Jepara Increasing every year, as many 0.64% in 2024 of reported cases increasing from 2023 while the incidence of complications was 0.58%.  There are various factors that influence the prevention of complications such as knowledge, eating behaviour, diet management of sufferers and physical activity. The need for control of prevention of complications of diabetes mellitus, especially in the lifestyle of the community in overcoming complications to reduce the morbidity of sufferers. The purpose of the study was to provides an overview of behaviors related to the practice of preventing complications of type 2 diabetes mellitus in the Jepara District Health Center area. Method: This analysis uses a quantitative approach with a cross-sectional study analysis method. The population analyzed was patients with type 2 diabetes mellitus aged 30-70 years at the Jepara District Health Center and a sample consisting of 115 people was selected through a simple random sampling technique. Data collection was carried out by questionnaire interviews and filling out the questionnaire research instrument by respondents. The result of the study showed that there was a patients' knowledge of Type 2 DM is good with a percentage value of 67.0%, have a eating behaviour with a percentage of 68.7%, have poor dietary management with a value of 53.9%, in addition, the most respondents have heavy physical activity 68.7%, and in the practice of preventing complications in Type 2 DM patients, the majority of Type 2 DM patients at the Jepara District Health Center have poor complication prevention practices of 64.3%. Based on this, it is expected that health workers will continue to provide assistance and support to improve the practice of preventing complications in patients with type 2 diabetes mellitus. Keywords:  Type 2 Diabetes Mellitus , Complication Prevention, Patient Knowledge, Eating Behaviour, Diet Regullation, Physical Activity